Exploring the Socio-Economic Implications of the Ban on Importing Used Clothes: Traders' Responses at Tanjung Balai TPO Market - Silalahi, Masna Sopiah; Delima, Delima; Tobing, Karisma (Institute for Law and Economics Studies, 2022)
This research examines the repercussions of the ban on importing used clothes into Tanjung Balai TPO Market, focusing on the responses of traders, shifts in consumer behavior, and broader socio-economic implications. The ban, enacted to address environmental concerns and foster local industry growth, triggered multifaceted changes within the marketplace. Employing a mixed-method approach, qualitative and quantitative data were gathered through interviews, surveys, and market analyses. The ban's impact was multifaceted, disrupting traders' operations, altering consumer access to affordable clothing, and prompting debates about the balance between policy objectives and socio-economic well-being. Unintended consequences, including challenges to livelihoods and alterations in market dynamics, underscored the complexity of policy interventions in trade ecosystems. Looking forward, the market's future is poised for further adaptations, digital integrations, and potential policy shifts balancing sustainability with community needs. The findings underscore the necessity for nuanced policy frameworks that reconcile environmental aspirations with socio-economic stability. The research illuminates the intricate interplay between policy interventions, market responses, and socio-economic equilibrium, emphasizing the traders' resilience and the evolving narrative within this dynamic marketplace.